ANALISIS ANGGARAN DAN REALISASI PENDAPATAN DAN BELANJA PADA BADAN LINGKUNGAN HIDUP DI KUTAI BARAT (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The purpose of this study to determine and analyze the performance of the management of budget and actual revenue and expenditure views from income of effectiveness ratio, the ratio of revenue growth, belanaja efficiency ratio and the ratio of spending growth.Data collection method in this study was conducted using field research and literature. The analytical tool used in this study uses the ratio of the effectiveness of the income, expenditure efficiency ratio, the ratio of revenue growth and expenditure growth rate. The results of this study demonstrate the effectiveness of the income equivalent of the Environment Agency in the Kutai Barat in 2013 until 2015, the year 2013-2014 results obtained are not effective in because realization of revenues achieved less than budgeted Environment Agency in the collection of revenue receipts not in accordance with the in budget. In 2014 the results obtained are less effective due to the realization of revenues achieved smaller than that in budget Environment Agency. The level of expenditure efficiency Environment Agency in 2013 s / d in 2015 Based on the calculation of the efficiency values fless than 100%, the budget savings go well or efficiency. Growth in revenue in 2014 amounted to (8.17%) means the realization of the budget revenues in 2014 decreased from the previous year. While the growth rate income Environment Agency in 2015 increased where the resulting percentage is equal to 9.23%. Of cause of revenue decreased in 2014 due to the budget that was obtained by local governments amounted to little compared to 2015. The growth rate of expenditure of the Environment Agency in 2015 decreased from the previous year. Environment Agency spending growth in 2014 s / d in 2015 from year-to-year fluctuations, this means spending growth rate experienced an unstable condition.Keywords: Effectiveness ratio analysis of income, expenditure efficiency ratio, the ratio of growth revenue and expenditure growth rate.